2011
DOI: 10.1161/circulationaha.110.984146
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Hyperlipidemia With a Genetic Switch Favorably Affects the Content and Inflammatory State of Macrophages in Atherosclerotic Plaques

Abstract: Background We previously showed that the progression of atherosclerosis in the Reversa mouse (Ldlr−/−Apob100/100Mttpfl/flMx1Cre+/+) was arrested when the hyperlipidemia was normalized by inactivating the gene for microsomal triglyceride transfer protein. Here we tested whether atherosclerosis would regress if the lipid levels were reduced after advanced plaques formed. Methods and Results Reversa mice were fed an atherogenic diet for 16 weeks. Plasma lipid levels were then reduced. Within 2 weeks, this reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
206
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(234 citation statements)
references
References 42 publications
25
206
2
1
Order By: Relevance
“…4), suggesting the difficulty of visualizing only M2 macrophages in distinction from nonpolarized macrophages by USPIO. Recently, it has been reported that the status of macrophage polarization in atherosclerotic plaques was dramatically changed in the progression and regression process of atherosclerosis using an experimental murine model (8,25). In addition, a substantial number of macrophages were polarized in those lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4), suggesting the difficulty of visualizing only M2 macrophages in distinction from nonpolarized macrophages by USPIO. Recently, it has been reported that the status of macrophage polarization in atherosclerotic plaques was dramatically changed in the progression and regression process of atherosclerosis using an experimental murine model (8,25). In addition, a substantial number of macrophages were polarized in those lesions.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that 18 F-FDG PET should dominantly visualize the M1 macrophage-infiltrated area. Some reports have suggested that 18 F-FDG PET may be useful to monitor the therapeutic effects of drugs (33)(34)(35), and some of the drugs are reported to affect the polarization of macrophages (8,36). Because therapies that reduce M1 macrophages are garnering more attention, it becomes increasingly important to select appropriate imaging methods that accurately detect plaque development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages CD16 + are usually related to a mature M2‐phenotype, also characterized for being positive for CD163 20 a scavenger receptor of the haemoglobin–haptoglobin complex involved in haeme catabolism through a process mediated by regulation of the haeme oxygenase‐1 (HMOX1) expression 79. The presence of CD163 macrophages in human atherosclerotic lesions has been also associated with anti‐inflammatory properties mediated through IL10 21, and studies in mice ApoE −/− models have associated plaque regression with the presence of M2 macrophage expressing CD163 80, 81, 82. Although differentiation of monocytes into macrophages is likely to be terminal, macrophages have the ability to switch phenotype and functional characteristics in response to external signals.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, immuno-LCM coupled with downstream gene or protein expression analysis has been used to study lesional macrophages in various stages of atherogenesis, including atherosclerosis regression. The inflammatory state of plaque macrophages was shown to be dynamically regulated as the severity of disease varied 144 . In humans, studies using LCM on surgical plaque explants has also identified genes implicated in lipid metabolism (such as FABP4 and LEP) and activation of the adipokine/peroxisome proliferator-activator receptor (PPAR) signalling pathways 145 , as well as a repertoire of inflammatory gene 'signatures' 146 , that might be important in mechanistic staging.…”
Section: Molecular Techniques-mentioning
confidence: 99%